Temporal and spatial variation in major ion chemistry and source identification of secondary inorganic aerosols in Northern Zhejiang Province, China - Xu, Jing-Sha; Xu, Meng-Xia; Snape, Colin; He, Jun; Behera, Sailesh N.; Xu, Hong-Hui; Ji, Dong-Sheng; Wang, Cheng-Jun; Yu, Huan; Xiao, Hang; Jiang, Yu-Jun; Qi, Bing; et al. (Elsevier, 2017)
To investigate the seasonal and spatial variations of ion chemistry of fine particles in Northern Zhejiang Province (NZP), China, one year-long field sampling was conducted at four representative sites (two urban, one suburb, and one rural sites) in both cities of Hangzhou and Ningbo from December 2014 to November 2015. Twelve water soluble inorganic ions (WSII) were characterized in this comprehensive study. The annual average of PM2.5 concentration in NZP as overall was 66.2 ± 37.7 μg m−3, and urban sites in NZP were observed with more severe PM2.5 pollution than the suburban and rural sites. The annual average concentration of total WSII at four sampling sites in NZP was 29.1 ± 19.9 μg m−3, dominated by SO42− (10.3 μg m−3), and followed by NO3− (8.9 μg m−3), NH4+ (6.6 μg m−3), Cl− (1.3 μg m−3) and K+ (0.7 μg m−3). Among all cations, NH4+ was the predominant neutralizing ion with the highest neutralization factor (NF), while the remaining cations showed limited neutralization capacity. The highest and lowest sulfur oxidation ratio (SOR) values in this region were found in summer and winter, respectively; while the seasonal patterns for nitrogen oxidation ratio (NOR) were opposite to that of SOR. Principal component analysis (PCA) showed that the significant sources of WSII in NZP were industrial emissions, biomass burning, and formation of secondary inorganic aerosols. In addition, contribution from transboundary transport of polluted aerosols was also confirmed from the assessment through air mass backward trajectory analysis.